Bereavement through substance use: findings from an interview study with adults in England and Scotland. (2nd September 2016) - Templeton, Lorna; Ford, Allison; McKell, Jennifer; Valentine, Christine; Walter, Tony; Velleman, Richard; Bauld, Linda; Hay, Gordon; Hollywood, Joan
Abstract: Background: Deaths associated with alcohol and/or drugs belong to a category of 'special' deaths due to three characteristics: traumatic circumstances of the death, stigma directed to both the bereaved and the deceased, and resulting disenfranchised grief experienced by the bereaved. These factors can impede those who are bereaved in this way from both grieving and accessing support. In response to a lack of research in this area this paper reports on an interview study that has aimed to better understand the experiences and needs of this neglected group of bereaved people. Method: Interviews with 106 adults (parents, children, spouses, siblings, nieces and friends) bereaved through substance use in Scotland and England. Results: Five themes describe interviewee experiences: possibility of death, official processes, stigma, grief and support. These findings suggest what is dominant or unique in this group of bereaved people; namely, that living with substance use (including anticipatory grief), experiencing the subsequent death (often traumatic and stigmatised) and the responses of professionals and others (more likely negative than positive) can disenfranchise grief and negatively impact bereavement and seeking support. Conclusions: This article describes a large and unique sample, the largest in the world to be recruited from this population. Our study raises awareness of a hitherto largely ignored and marginalised group of bereaved people, highlighting what might be particular to their bereavement experience and how this may differ from other bereavements, thereby providing an evidence base for improving the availability, level and quality of support.